The Resource Potential and Development Prospect of Helium in Changqing Gas Field. (23rd July 2022) - Wang, Dahai; Li, Jinbu; Yu, Zhanhai; Zhang, Ji; Liu, Lili; Xiao, Feng; Shan, Changan
Abstract : Helium, a rare gas widely applied in high-tech fields, is a significant strategic resource in China. The foreign-trade dependence ratio of helium in China is 95%. The work reviewed the applications and market analysis of helium and reservoir modeling and distribution of helium in Changqing Gas Field as well as the helium extraction techniques from natural gases. According to the analysis of the component test and the dynamic monitoring of exploited gas wells and gas-gathering stations, the average helium content in Changqing Gas Field was 0.028%. Helium was rich in the northwest of Changqing Gas Field, but poor in the central and eastern regions. The helium volume contents in Qingyang Gas Field, Huanglong Gas Field, and the central, western, and southern regions of Sulige Gas Field have reached the industrial development standard. PetroChina performed the economic-feasibility evaluation and production-factor matching research on helium development and selected Changqing Gas Field as the demonstration for development. A large helium plant was established in Changqing Gas Field using the cryogenic method with/without membrane separation for helium extraction. Then, a helium development scheme was formulated and implemented to build the industry chain of helium in China. Changqing Gas Field is rich in helium resources. Developing helium has entered a strategic period with the technological advancement in extracting helium from natural gases and the increased prosperity of the international helium market. There are broad prospects and great benefits to exploiting helium resources in Changqing.